Duct Diameter and Size of Stones Predict Successful Extracorporeal Shock Wave Lithotripsy and Endoscopic Clearance in Patients With Chronic Pancreatitis and Pancreaticolithiasis. Issue 8 (September 2016) - Lapp, Robert T.; Wolf, J. Stuart; Faerber, Gary J.; Roberts, William W.; McCarthy, Sean T.; Anderson, Michelle A.; Wamsteker, Erik-Jan; Elta, Grace H.; Scheiman, James M.; Kwon, Richard S.
Abstract : Objectives: The need for endoscopic therapy before extracorporeal shock wave lithotripsy (SWL) to facilitate pancreatic duct stone removal is unclear. Predictive factors associated with successful fragmentation and subsequent complete duct clearance are variable. We hypothesize pancreatic duct strictures and large stones, but not pre-SWL endotherapy, correlate with successful fragmentation and complete duct clearance. Methods: A retrospective cohort study of patients with pancreaticolithiasis who underwent SWL and endoscopic retrograde cholangiopancreatography between January 2009 and June 2014 was evaluated. Results: Thirty-seven patients were treated. Technical success (TS) of fragmentation was achieved in 22 patients (60%). Technical success was associated with fewer stones and SWL sessions and smaller stone and duct size. By multivariate logistic regression, only duct dilation was associated with TS. Endoscopic success of complete duct clearance was achieved in 29 patients (80%). Endoscopic success was more frequent with stones 12 mm or less and with successful TS. By multivariate logistic regression, stones greater than 12 mm were associated with endoscopic failure. Conclusions: Pre-SWL endotherapy does not affect stone fragmentation. Patients with a dilated duct (>8 mm) and pancreatic stones 12 mm or greater were associated with unsuccessful TS and endoscopic success, respectively, and may benefit from early referral for surgical decompression.